Study to determine serum vitamin D levels in patients with congestive heart failure - Wadhera, Nishant; Kalra, Geetika; Gupta, Abhishek; Singhal, Saurabh; Jha, S. K. (International Journal of Research in Medical Sciences, 2019)
Background: It was to evaluate the association of serum levels of vitamin D in patients with congestive heart failure. Methods: The present study was conducted in the department of Medicine at Chattrapati Shivaji Subharti Hospital among 100 patients, aged 18 years and above diagnosed as congestive heart failure on the basis of clinical and echocardiographic evidence. Clinical manifestations looked for CHF were: Dyspnea, orthopnea, acute pulmonary edema, cerebral symptoms, cheyne-stokes respiration, cyanosis, sinus tachycardia, raised jugular venous pressure, congestive hepatomegaly and pedal edema. In the present study deficiency/ insufficiency of vitamin D was considered when the presence of levels of 25-hydroxyvitamin D was <30 ng/ml. Laboratory tests performed to diagnose congestive heart failure and serum vitamin D levels were complete blood count, KFT (urea, serum creatinine), serum electrolytes, ECG, chest X ray and echocardiogram. Data were tabulated and examined using the statistical package for Social Sciences Version 22.0. Results: When data was assessed for comparison in relation to NHYA grades and vitamin D levels, it was found to be statistically significant. The Mean±SD scores of serum urea (mg/dL) was found to be 44.7±56.4, 47.3±63.8 and 36.4± 18.3 in whole study sample, vitamin D levels <30 and vitamin D levels >30 respectively with statistically significant difference. The Mean±SD scores of CPK MB (IU/L) was found to be 33.1±20.8 and 18.6±13.3 among the subjects having vitamin D levels <30 and vitamin D levels >30 respectively with statistically significant difference. Conclusions: The results of the present study suggest that low levels of vitamin D may adversely affect the cardiovascular system.